Pengaruh Leverage dan Profitabilitas pada Pengungkapan Manajemen Risiko - Saskara, I Putu Wahyu; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2018)
Risk is an adherent thing so that information shared by the company hoped to decrease the risk level and uncertainty faced by the stakeholders, therefore effective disclosure was necessary. This research was aimed at obtaining empirical evidence, leverage effect and profitability upon risk management disclosure. Population of this research was all companies registered at LQ45 Index in BEI during 2012-2016 period. Sampling was conducted using nonprobability sampling method with purposive sampling technique. Data were collected using documentation method. Data analysis was conducted using double-regression analysis technique. The result of this research showed that leverage has positive effect upon risk management disclosure, so that the higher the leverage, the wider the risk management disclosure done by the company. Profitability was also discovered to have positive effect upon the risk management disclosure, therefore the higher the profitability, the wider the risk management disclosure. Keywords : stakeholder theory, agency theory, risk management disclosure, leverage, profitability